2016
DOI: 10.1016/j.drugalcdep.2016.01.024
|View full text |Cite
|
Sign up to set email alerts
|

New psychoactive substance use among regular psychostimulant users in Australia, 2010–2015

Abstract: NPS use has been established as a significant and ongoing practice amongst our sample of RPU. It appears that RPU seek out NPS with similar properties to the illicit drugs that they are already consuming, with poly NPS consumers found to be a particularly high risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 30 publications
4
45
0
Order By: Relevance
“…A previous study of self-reported NPS use in a US nationally representative sample found that 79.4% of NPS users reported lifetime ecstasy/3,4-methylenedioxymetham-phetamine (MDMA) use and 73.7% reported LSD use, with even higher prevalence among those reporting use of tryptamines or psychedelic phenethylamines (18). A recent European study found that ecstasy users were more likely to report use of phenethylamines and that LSD users were more likely to report use of phenethylamines and tryptamines (38), and an online survey of mephedrone users found that 87% had used ecstasy and 11% typically co-used mephedrone with ecstasy (39). While drugs such as “bath salts” may have similar effects to drugs such as ecstasy, ecstasy is also commonly adulterated with such NPSs (4042).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of self-reported NPS use in a US nationally representative sample found that 79.4% of NPS users reported lifetime ecstasy/3,4-methylenedioxymetham-phetamine (MDMA) use and 73.7% reported LSD use, with even higher prevalence among those reporting use of tryptamines or psychedelic phenethylamines (18). A recent European study found that ecstasy users were more likely to report use of phenethylamines and that LSD users were more likely to report use of phenethylamines and tryptamines (38), and an online survey of mephedrone users found that 87% had used ecstasy and 11% typically co-used mephedrone with ecstasy (39). While drugs such as “bath salts” may have similar effects to drugs such as ecstasy, ecstasy is also commonly adulterated with such NPSs (4042).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of SCRA-related posts echoes the decrease of SCRA consumption observed over the past few years in the countries from where most of the Web forums users are geolocated (U.S. (Johnston, Miech, O'Malley, Bachman, & Schulenberg, 2015), U.K (U.K Home Office, 2016), Australia (Sutherland, et al, 2016)). Our longitudinal analysis demonstrates that positive effect (i.e., “High” and “Euphoria”) proportions continuously decreased since 2008.…”
Section: Discussionmentioning
confidence: 72%
“…Australian and state legislation has since been modified, banning the importation and sale of synthetic cannabinoids and other new psychoactive substances, although there are indications that the use of NPS continues in some parts of the community (Sutherland et al . ).…”
Section: Introductionmentioning
confidence: 97%